DIET-RELATED RELATIONSHIP PRESSURE AND CONFLICT: GENERATIONAL DIFFERENCES IN THE MODERATING EFFECTS OF MINDFULNESS. Issue 4 (1st October 2020) - Seidel, Amber J.; Leavitt, Chelom E.; Hansen, Denise; Gill, Sukhdeep
Abstract : A committed partner is a central relationship throughout adulthood and may have important health and relationship implications. More specifically, being pressured by a partner to change lifestyle behaviors (e.g., diet) can have negative effects on a relationship. Building on the life course perspective, this study examined individual mindfulness, the ability to remain aware in the present moment, as a buffer of the negative effects of partner pressure to change on relationship conflict. Data were collected from a community sample of younger and older adults (N = 362). Findings reveal that mindfulness moderated the association between partner pressure and relationship conflict for younger, but not older, adults. Specifically, younger adults with higher levels of mindfulness showed less relationship conflict with partner pressure, whereas younger adults with lower levels of mindfulness showed more relationship conflict. These findings have implications for interpersonal interactions and suggest that being aware and mindful may encourage better relationship quality, particularly for younger adults. More work is needed to understand the mechanisms that may be contributing to older adult relationship well-being.